KRESEK MAN IN ACTION: MOTIVE OF ENVIRONMENT CARE ACTION ON CELEBRATION OF THE BLITAR DJADOEL - Fredianto, Dadang (University of Muhammadiyah Malang, 2019)
Blitar Djadoel Celebration always successful every year. But the success is inseparable from the classic problems that accompany it. In 2019, the trash phenomenon at Blitar Djadoel became viral on social media because of the bad behavior of visitors. Unexpectedly, the phenomenon was increasingly viral due to the action of Kresek Man who picked up trash in the Blitar Djadeol area. This study aims to determine the motive for the action of Kresek Man with the Motive Concept (because motive and in order to motive) introduced by Alfred Schutz. This qualitative research with a phenomenological approach takes data through observation techniques, in-depth interviews, observations on social media and documentation. This study found that there was a motive for Kresek Man actions that were seen in general and specifically. The action motives in general can be known through the reason Kresek Man performs the action as a whole. While special motives can be known through the reason of Kresek Man in selecting super hero costumes and figures, reasons for hiding identities, reasons for documenting the actions and reasons for making trash monuments. This research reveals that in each of these motives there are not always two types of motives,